Data on metal-chelating, -immobilisation and biosorption properties by Gordonia rubripertincta CWB2 in dependency on rare earth adaptation - Schwabe, Ringo; Senges, Christoph Helmut Rudi; Bandow, Julia Elisabeth; Heine, Thomas; Lehmann, Henry; Wiche, Oliver; Schlömann, Michael; Levicán, Gloria; Tischler, Dirk (Data in brief, 2020)
Recent studies have shown that the metal adaptation of Actinobacteria offers a rich source of metal inducible environmentally relevant bio-compounds and molecules. These interact through biosorption towards the unique cell walls or via metal chelating activity of metallophors with trace elements, heavy metals and even with lanthanides to overcome limitations and toxic concentrations. Herein, the purpose is to investigate the adaptation potential of Gordonia rubripertincta CWB2 in dependence of the rare earths and to determine if we can utilize promising metallophore metal affinities for metal separation from aquatic solutions. For details on data interpretation and applicability of siderophores we refer to the related article entitled “Cultivation dependent formation of siderophores by Gordonia rubripertincta CWB2” [1]. The respective workflow comprises a metal adaptation method to demonstrate effects on bacterial growth, pH, metallophore production, and metabolic change. All this was evaluated by LC-MS/MS and effects on biosorption of rare earths was verified by ICP-MS. Furthermore, we were able to carry out batch metal adsorption and desorption studies of metallophores entrapped in inorganic polymers of tetramethoxysilane (TMOS) to determine metal chelating capacities and selective enrichment effects from model solutions. The adaptation potential of strain CWB2 at increased erbium and manganese concentrations was verified by increased chelating activity on agar plates, in liquid assays and demonstrated by the successful enrichment of erbium by metallophore-functionalized TMOS-polymers from an aquatic model solution. Furthermore, the number of detected compounds in dependency of rare earths differ in spectral counts and diversity compared to the wild type. Finally, the biosorption of rare earths for the selected adaptation was increased significantly up to 2-fold compared to the wild-type. Overall a holistic approach to metal stress was utilised, integrating a bacterial erbium adaptation, metal chelating, biosorption of lanthanides and immobilization as well as enrichment of metals using metallophore functionalized inorganic TMOS polymers for separation of metals from aquatic model solutions.